Workers, warriors and criminals: Social conflict in general equilibrium - Ernesto Dal Bó; Pedro Dal Bó (Brown University, Department of Economics, 2004)
We analyze how economy-wide forces (i.e.shocks to terms of trade, technology and endowments) affect the intensity of social conflict. We see conflict phenomena such as crime and civil war as involving resource appropriation activities. We show that not all shocks that could make society richer will reduce conflict. Positive shocks to labor intensive industries will diminish social conflict, while positive shocks to capital intensive industries will increase it. The key requirement is that appropriation activities be more labor intensive than the economy. Our model can explain the positive association between crime and inequality, and the curse of natural resources; it predicts that aid in kind to war-ridden societies will have perverse effects, and offers guidance on how to integrate international trade policy and peacekeeping efforts. Including appropriation activities into a canonic general equilibrium model introduces a social constraint to policy analysis. Thus, we can also account for populist policies, apparently inefficient redistribution and “national development strategies”. – conflict ; civil war ; crime ; social constraint ; populism ; trade policy ; inefficient redistribution
Keywords: D72; D74; D78; F13; H23; K42; O1; 330; Sozialer Konflikt; Bürgerkrieg; Kriminalität; Außenhandelspolitik; Einkommensumverteilung; Gleichgewicht; Theorie